INSTITUTIONALIZATION AND PHASHING MODEL OF HISTORICAL DEVELOPMENT OF STATE EMPLOYMENT POLICY (USING THE EXAMPLE OF ECONOMICALLY DEVELOPED WESTERN COUNTRIES) - Фесенко, Артур; Чорна, Вікторія; Бондарець, Богдан (Modern engineering and innovative technologies, 2025)
Within the framework of this article, an attempt is made to reveal the historical path of formation, development and evolution of state employment policy in economically developed countries with a market economy (capitalist countries of Europe and the USA